A comparative investigation on H3K27ac enhancer activities in the brain and liver tissues between wild boars and domesticated pigs. (16th August 2022) - Zhou, Zhimin; Jiang, Tao; Zhu, Yaling; Ling, Ziqi; Yang, Bin; Huang, Lusheng
Abstract: Dramatic phenotypic differences between domestic pigs and wild boars ( Sus scrofa ) provide opportunities to investigate molecular mechanisms underlying the formation of complex traits, including morphology, physiology and behaviour . Most studies comparing domestic pigs and wild boars have focused on variations in DNA sequences and mRNA expression, but not on epigenetic changes. Here, we present a genome‐wide comparative study on H3K27ac enhancer activities and the corresponding mRNA profiling in the brain and liver tissues of adult Bama Xiang pigs (BMXs) and Chinese wild boars (CWBs). We identified a total of 1, 29, 487 potential regulatory elements, among which 11, 241 H3K27ac peaks showed differential activity between CWBs and BMXs in at least one tissue. These peaks were overrepresented by binding motifs of FOXA1, JunB, ATF3 and BATF, and overlapped with differentially expressed genes that are involved in female mating behaviour, response to growth factors and hormones, and lipid metabolism. We also identified 4118 nonredundant super‐enhancers from ChIP‐Seq data on H3K27ac. Notably, we identified differentially active peaks located close to or within candidate genes, including TBX19, MSTN, AHR and P2RY1, which were identified in DNA sequence‐based population differentiation studies. This study generates a valuable dataset on H3K27ac profiles of the brain and liver from domestic pigs and wild boars, which helps gain insights into the changes in enhancer activities from wild boars to domestic pigs.